Nucleolar-persistence phenomenon during spermatogenesis in genus Meccus (Hemiptera, Triatominae) - Madeira, F. F. [UNESP]; Lima, A. A. C. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP]; Alevi, K. C. C. [UNESP] (Funpec-editora, 2016)
The Triatominae subfamily consists of 150 species in 18 genera, grouped into six tribes. In cytogenetics, triatomines are important biological models because they have holocentric chromosomes and nucleolar persistence in meiosis. The phenomenon of nucleolar persistence has been described for 23 species of triatomine in three genera: Triatoma, Rhodnius, and Panstrongylus. However, new species and genera should be analyzed to assess whether nucleolar persistence is a peculiarity of Triatominae. Thus, this study aimed to analyze nucleolar behavior during spermatogenesis of Meccus pallidipennis and M. longipennis, focusing on the nucleolar-persistence phenomenon. Through the analysis of spermatogenesis, more specifically of meiotic metaphase, we observed the phenomenon of nucleolar persistence in M. pallidipennis and M. longipennis, represented by remnants of nucleolar material in metaphase. Thus, although nucleologenesis of new species, and, especially, new genera, should be analyzed, this study confirms for the first time the phenomenon of nucleolar persistence in the genus Meccus. Therefore, we emphasize the importance of new studies in this area in order to assess whether this phenomenon is truly a synapomorphy of these hematophagous insects.
Keywords: Cytogenetics; Nucleolus; Meiosis